No way home: silence, slowness and the problem of authenticity in the cinema of Lisandro Alonso - Roberto Cavallini (Aniki: Revista Portuguesa da Imagem em Movimento, 2015)
In his trilogy, comprising La Libertad (2001), Los Muertos (2004) and Liverpool (2008), Argentinian director Lisandro Alonso employs a distinctive narrative motif, namely the journey of solitary individuals through desolated landscapes in rural Argentina. From a comparative view, the key to understanding these introverted trajectories is to consider Alonso’s construction of narrative space around the misery of a stark void, namely the absence of home. For Alonso, home is not a peaceful destination, connoting the intimacy of a family, serenity or simply a place where one is allowed to dream in peace (Bachelard). The absence of home becomes the blind spot of these journeys: home turns out to be a broken horizon. In this essay I will mainly focus on the film Los Muertos and the way in which it radicalizes narrative space through the combination of cinematic silence (absence of words and dialogues) and cinematic slowness (static long-takes) while formulating a void which coincides with the protagonist’s homelessness. Moreover, this essay tries to consider how Alonso’s radical cinematic realism problematizes the concept of authenticity in its modern formation, and also in the context of Rancière’s notion of documentary fiction and the relationship between aesthetics and politics.